Advances in chemical engineering. - Marin, Guy B. (Advances in chemical engineering, 2007)
Understanding and modeling the kinetics of chemical reactions is crucial to any research and development effort aimed at process optimization and innovation. This volume provides four complementary points of view. It reflects state-of-the-art developments as well as views on the way to proceed by reporting on the efforts of a representative, sample of research and development groups. A first contribution by W.H. Green Jr. sets the scene. The author advocates a paradigm shift in chemical kinetics from "postdictive" to predictive models. The contribution from the Politecnico di Milano reports on the tremendous experience accumulated over the years in the field of steam cracking, one of the largest scale production processes of the petrochemical industry. The Russian school of chemical kinetics is represented by a chapter on oxidation of alkanes, this contribution addresses more "philosophical" issues. The last chapter gives an indication of the state-of-the-art in an industrial environment. * Provides original reviews * Presents leading chemical engineers as authors * Reviews state-of-the-art developments.